Ruprecht 55: An OB association at the edge of our Galaxy - Bosch, Guillermo Luis (2003)
We present new spectroscopy in the optical range and 21-cm Hi data covering the Ruprecht 55 (Ru 55) field in the Puppis window where several authors have proposed the existence of one (or two) clusters. We have determined new MK spectral types for about 50 stars in the region, finding 43 OB-type stars among them. LS 985 was found to be an O9 V + 09.5 III binary and it is the earliest type of star in our observed sample. We have identified a stellar OB association (Ru 55), which is most likely related to a depletion detected in our H I data, as: (i) they are located at the same distance (6 kpc), within observational errors; (ii) both have similar radial velocities (∼67 km s-1); (iii) current OB stars could have provided the energy needed to blow the cavity; (iv) the dynamical time-scale for the hole buildup matches the age estimated for the earliest OB stars; and (v) LS 985 might be responsible for ionizing the Hi cavity inner walls close to it.